(untitled) (XXI Century. Spanish Literature and Culture, 2024)
The catalonian philologist José María Balcells (Barcelona, 1943) transcribes, annotates and comments in this article five unpublished epistolary documents from his personal file and from Fundación Jorge Guillén of Valladolid. These letters bear witness to the communication that was kept whit the poet Ángel Crespo (1926-1999) of Ciudad Real during the years 1976-1977. This epistolary relationship started in December of 1974 and continued during the two years mentioned, and grew through a warm exchange of information regarding the teaching activities, investigation projects, philological editions in progress, and in regards to other types of writings.